Surgical treatment of locally advanced right colon cancer invading neighboring organs - Ri, HyokJu; Kang, HaoNan; Xu, ZhaoHui; Gong, ZeZhong; Jo, HyonSu; Amadou, Boureima Hamidou; Xu, Yang; Ren, YanYing; Zhu, WanJi; Chen, Xin (Frontiers in Medicine, 2023)
Purpose Invasion of the pancreas and/or duodenum with/without neighboring organs by locally advanced right colon cancer (LARCC) is a very rare clinical phenomenon that is difficult to manage. The purpose of this review is to suggest the most reasonable surgical approach for primary right colon cancer invading neighboring organs such as the pancreas and/or duodenum. Methods An extensive systematic research was conducted in PubMed, Medline, Embase, Scopus, and the Cochrane Central Register of Controlled Trials (CENTRAL) using the MeSH terms and keywords. Data were extracted from the patients who underwent en bloc resection and local resection with right hemicolectomy (RHC), the analysis was performed with the survival rate as the outcome parameters. Results As a result of the analysis of 117 patient data with locally advanced colon cancer (LACC) (73 for males, 39 for females) aged 25–85 years old from 11 articles between 2008 and 2021, the survival rate of en bloc resection was 72% with invasion of the duodenum, 71.43% with invasion of the pancreas, 55.56% with simultaneous invasion of the duodenum and pancreas, and 57.9% with invasion of neighboring organs with/without invasion of duodenum and/or pancreas. These survival results were higher than with local resection of the affected organ plus RHC. Conclusion When the LARCC has invaded neighboring organs, particularly when duodenum or pancreas are invaded simultaneously or individually, en bloc resection is a reasonable option to increase patient survival after surgery.